An Analytical Study of Twak Sharir in Ayurveda with Correlation to Modern Dermatology and Histology - Kumari, Dezi; Gupta, S. S.; Raj, Piyush; Kumari, Sommya; Kumar, Mukesh; Suresh, Aswin (Journal of Neonatal Surgery, 2025)
Twak (skin) is one of the essential anatomical and functional entities discussed in Rachana Sharir of Ayurveda. Ancient seers have elaborated the multi-layered structure of Twak in terms of its origin (Utpatti), types (Saptadhatuja Twak), location, and physiological relevance. In modern biomedical science, the skin is the largest organ of the body and is extensively studied in terms of its histology, function, and pathology. This article attempts to bridge the traditional Ayurvedic descriptions of Twak Sharir with the contemporary understanding of dermatology and histology, highlighting parallels, complementarities, and unique insights.